Vagueness and pragmatic reasoning in quantified sentences - Cremers, Alexandre (Proceedings of the Amsterdam Colloquium, 2024)
Vagueness has been extensively studied as a standalone topic, but little is known of its interactions with other semantic and pragmatic phenomena. We present an experiment testing a Rational Speech-Act model from Cremers (2022) which aims to offer a general account of the pragmatic use of vague sentences and the implicatures they give rise to on a new class of sentences where a vague term restricts a universal quantifier. We found that an implicature predicted by the model is present, but a separate prediction on borderline cases isn’t verified. We discuss consequences for the modeling of pragmatic uses of vague sentences.